The extraction of phenolics from hibiscus sabdariffa linn - Ahmad Latif, Athirah (2017)
This study is to introduce the phenolic compound in H. sabdariffa. The medicinal properties of the phenolic compound were reported as antihypertensive, antigastric ulcer, antioxidant, antimicrobial and antihyperlipidemia. The research objectives are to extract the calyces of H. sabdariffa to obtain the crude extract, investigate the components in H. sabdariffa, analyse the suitable medium of the extract of H. sabdariffa in acidic and basic medium and analyse the structure of phenolic compound in H. sabdariffa. From the literature review, the phenolics are the most abundant compound in H. sabdariffa. The community pharmacy also provides this herb as neutraceutical and pharmaceutical products. The methodology in this study are the extraction of the H. sabdariffa, compound profiling by using the Thin Layer Chromatography technique, testing in acidic and basic medium and detection of the phenolic compound by using UV - VIS spectrometer. The colors of H. sabdariffa extracts were changed when HCl and NaOH were added. The UV spectra of the H. sabdariffa in acidic medium and basic medium demonstrated a hypochromic shifting. However, the same curve for extract in neutral and acidic medium indicates that it has same structure of compound. The same value of the retention factor in the monograph and laboratory experiment suggests that the sample contains delphinidine-3- sambubioside. Special precautions need to be taken since the stability of the H. sabdariffa extract is low. The hypotheses are accepted. More research needs to be performed on H. sabdariffa. It is hoped that this study could provide know ledge on H. sabdariffa.